The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jtemb.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mercury and autism: A comprehensive review and discussion

Abstract: The brain pathology in autism spectrum disorders (ASD) indicates marked and ongoing inflammatory reactivity with concomitant neuronal damage. These findings are suggestive of neuronal insult as a result of external factors, rather than some type of developmental mishap. Various xenobiotics have been suggested as possible causes of this pathology. In a recent review, the top ten environmental compounds suspected of causing autism and learning disabilities were listed and they included: lead, methyl-mercury, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 125 publications
2
49
1
6
Order By: Relevance
“…A significant overall association between environmental Hg exposure during prenatal or infant periods and autism risk was found in a recently published meta-analysis (odds ratio=1.66 95% confidence interval=1.14–2.17) [18]. Finally, a recent critical review of the more than 90 studies published from 1999 to 2016 that examined the potential relationship between Hg and autism found that 74% supported the link [19]. By contrast, there are studies that did not link Hg exposure with the long-term risk of a child being diagnosed with autism, but these studies have been criticized for their potential methodological limitations [12] and potential conflicts of interest [20].…”
Section: Discussionmentioning
confidence: 99%
“…A significant overall association between environmental Hg exposure during prenatal or infant periods and autism risk was found in a recently published meta-analysis (odds ratio=1.66 95% confidence interval=1.14–2.17) [18]. Finally, a recent critical review of the more than 90 studies published from 1999 to 2016 that examined the potential relationship between Hg and autism found that 74% supported the link [19]. By contrast, there are studies that did not link Hg exposure with the long-term risk of a child being diagnosed with autism, but these studies have been criticized for their potential methodological limitations [12] and potential conflicts of interest [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mercury, then, has repeatedly been proposed as a cause of autism. A review of the literature by Kern [21] reveals that a large majority of the work (approx. 74%) under consideration took into account the role of mercury as a risk factor for ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies implicate vaccines or thimerosal therein. One review found a high correlation between mercury exposure and autism (1). Another review totes "shifting hypotheses" in an unproven vaccine story (2).…”
Section: Introductionmentioning
confidence: 99%